Snow-Covered Tires Generate Microhabitats That Enhance Overwintering Survival of Aedes albopictus (Diptera: Culicidae) in the Midwest, USA. Issue 3 (11th May 2022) - Susong, Katie M; Tucker, Bradley J; Bron, Gebienna M; Irwin, Patrick; Kirsch, John Mitchell; Vimont, Daniel; Stone, Chris; Paskewitz, Susan M; Bartholomay, Lyric C
Abstract: The Asian tiger mosquito, Aedes albopictus (Skuse), is a public health threat because it can potentially transmit multiple pathogenic arboviruses, exhibits aggressive diurnal biting, and is highly invasive. As Ae. albopictus moved northward into the United States, the limits of expansion were predicted as locations with a mean January temperature warmer than −2.5°C. We postulated that the range of Ae. albopictus could exceed these temperature limits if eggs in diapause overwinter in tires that provide an insulating effect from extreme temperatures. Fifteen tires with Ae. albopictus and Aedes triseriatus (Say) eggs, a native cold hardy species, were placed outside at five locations along a latitudinal gradient in Wisconsin and Illinois during the winter of 2018–2019; notably, in January 2019, a regional arctic air event brought the lowest temperatures recorded in over 20 yr. External and internal tire temperatures were recorded at 3 hr intervals, and egg survival was recorded after six months. Aedes albopictus eggs survived only from tires at northernmost locations. The mean internal January temperature of tires that supported survival was −1.8°C, while externally the mean temperature was −5.3°C, indicating that tires provided an average of +3.5°C of insulation. Tires that supported egg survival also had over 100 mm of snow cover during January. In the absence of snow cover, tires across the study area provided an average +0.79°C [95% CI 0.34–1.11] insulation. This work provides strong argument for the inclusion of microhabitats in models of dispersal and establishment of Ae. albopictus and other vector species.